Poor women in rich countries the feminization of poverty over the life course - Goldberg, Gertrude S. (New York ; Oxford : Oxford University Press, 2010)
This wide-ranging collection focuses on the economic condition of single mothers and single elderly women in eight wealthy but diverse countries: Canada, France, Germany, Italy, Japan Sweden, the United Kingdom, and the United States.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Poor women -- Developed countries -- Cross-cultural studies; Women heads of households -- Developed countries -- Cross-cultural studies; Poverty -- Developed countries -- Cross-cultural studies; Single women -- Developed countries -- Economic conditions -- Cross-cultural studies